2010
DOI: 10.1111/j.1756-5391.2010.01056.x
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for reporting adverse drug reactions and adverse events of traditional Chinese medicine

Abstract: Clearly report adverse effect or adverse event occurred in the clinical practice is very important for understanding the potential risk of using a drug for treatment of diseases, and with other advantages. This document aims to help healthcare providers to organize, report, and publish information on ADR/AE occurrences and to identify the nature of the ADR/AE in TCM and integrative medicine practice. This document provides recommendations on constructing a title, basic factors of writing an abstract and the te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…However, the applications may be largely dependent on the clinician’s experience, which may limit the application of same decoction by different clinicians to different patients. The condition may explain the frequently occurred adverse events in application of particular traditional medicine ( Wang et al, 2010 ; Wu et al, 2010 ; Hwang et al, 2018 ). Moreover, the bioactive ingredients of the decoctions have not been fully identified and studied in independent experiments.…”
Section: Limitations and Possible Solutionsmentioning
confidence: 99%
“…However, the applications may be largely dependent on the clinician’s experience, which may limit the application of same decoction by different clinicians to different patients. The condition may explain the frequently occurred adverse events in application of particular traditional medicine ( Wang et al, 2010 ; Wu et al, 2010 ; Hwang et al, 2018 ). Moreover, the bioactive ingredients of the decoctions have not been fully identified and studied in independent experiments.…”
Section: Limitations and Possible Solutionsmentioning
confidence: 99%
“…Shuanghuanglian injection is usually used for the treatment of respiratory infection and has been one of the top selling herbal medicine products over the last decade 17 . However, Shuanghuanglian injection often causes severe allergic reaction in the clinic [18][19][20] . Recent study had shown that, the cosolvent Tween-80 in herbal injection is the main inducement of allergic reaction and the medical shock 21,22 .…”
Section: Determination Of 5-ht In Allergic Guinea Pig Plasmamentioning
confidence: 99%
“…Problems concerning the choice and reporting of outcome measures for clinical trials of TCM were summarized as follows [ 5 , 8 – 10 ]. (1) Outcome measured and reported in clinical trials of the same condition varied greatly, and there was apparent selective reporting bias.…”
Section: Problems With Outcome Measures In Clinical Trials Of Tcmmentioning
confidence: 99%